Peningkatan Nilai Tambah Bawang Merah melalui Kegiatan ReFORm pada Kelompok Wanita Tani (KWT) Warga Massenrempulu, Kabupaten Enrekang, Provinsi Sulawesi Selatan - Nurlela Machmuddin; Eka Merdekawati; Made Gayatri; Andini T. Tunggadewi (To Maega : Jurnal Pengabdian Masyarakat, 2024)
There is an increase in red onions production in Enrekang Regency every year. However, the current abundant red onion production is not balanced by an increase in the selling price of red onions which continues to fluctuate. Efforts are needed to increase the added value of red onions which are expected to provide new job opportunities that can increase community income. Efforts to achieve this goal are carried out through community service activities that carry the term reFORm. Reform activities consist of processing red onions products (re-change), processing red onions waste (re-cycle), calculating cost or sales prices (re-account), and marketing processed red onions (re-market). Service activities are carried out with a program implementation scheme through socialization and education, providing training, mentoring and evaluation. The implementation of activities carried out at the KWT Supplir production house with participants from KWT Supplir, and KWT Mekar Jujur Pararuk. The results of activities ranging from socialization to evaluation produced output in the form of improved packaging, the formation of a social media account for KWT Supplir as a forum to market their products and for KWT Meker Jujur, they have added to their KWT activities by starting to produce fried red onoins that are ready and suitable for the market